Employee Performance In Public Service At The Malua District Office, Malua District, Enrekang District - ., ratna; Andi Cudai Nur; Andi Muhammad Rivai (Universitas Negeri Makassar, 2025)
This study aims to obtain information related to public services directly related to employee performance and to seek information related to the drivers of high-performance employees. This study uses a descriptive qualitative method with documentation, observation, and interviews as the methods for data collection. Analysis of findings by presenting data that has been previously grouped so that conclusions can be drawn from the field with additional SWOT analysis. The findings of this study are that the Malua District Office, Enrekang Regency, has employees who are ineffective in carrying out their work due to limited human resources, information between employees has been well managed, the community served is not in a timely manner because office management is not efficient, there are still many employees who have not achieved work targets according to the specified deadline and employees have been optimal in work initiatives. Employees are encouraged to progress because they are motivated to progress together and the work environment is supportive. Barriers to employee growth are limited human resources, synergy between colleagues is not strong, and work networks have not been formed. An aggressive strategy is a way to improve employee performance by conducting regular training to optimize employee performance.